Factors influencing academic performance of pharmacy students at Universiti Teknologi MARA (UiTM) Selangor Malaysia / Ismail Mohd Shah and Nursyahmina Zamri - Mohd Shah, Ismail; Zamri, Nursyahmina (Faculty of Pharmacy, 2021)
Students' academic performance is one of the fundamental concerns as outstanding academic performance can be proof of the intellectuality of those students. The purpose of this study is to assess the correlation of the academic performance of students between student factors, family factors, university infrastructure factors, and faculty factors. This study used a stratified sampling design that was carried out through a questionnaire. The collected data was analyzed by the Social Sciences Statistical Package (SPSS) and the degree of relationship between factors that affect academic performance with the academic performance of students was evaluated by the weighted mean. Three domain factors, lecturer factors with a mean of 4.01, university infrastructure factors (3.91), family factors (3.35), and the three subdomains include learning techniques (3.68), academic interest and motivation (3.32), and student's attitude (3.05) were found to have a varying impact upon pharmacy student's and significant influence on their academic achievement as well. This result is primarily important because it can be used by academic administrators and lecturers as a basis to devise and execute an intervention plan aimed at allowing pharmacy students to enhance their academic performance. Students will be more aware of potential factors that may influence their academic performance.